ESSENTIAL PROPERTIES RELATED TO SHORT-TIME FRACTIONAL FOURIER TRANSFORM - SULASTERI, SRI; BACHTIAR, NASRULLAH; EKASASMITA, WAHYUNI (Departemen Matematika dan Sains Data FMIPA Universitas Andalas Padang, 2024)
We start by defining the short-time fractional Fourier transform in this paper, which is a natural generalization of the fractional Fourier transform. We then investigate its essential properties and explore an uncertainty principle related to this proposed transformation.